Effectiveness of a 30° Head-Up Position for Lowering Headache Severity in Mild Head Injury - Ningsih, Bayu; Wahyuningsih, Indri (Asosiasi Dosen Muda Indonesia, 2025)
This single case study evaluated the effect of a 30° head-up position on headache and vital signs in a 16-year-old male with mild head injury presenting to the Emergency Department of RSUD Kanjuruhan, Kepanjen (21 June 2025). The non-pharmacological intervention head elevation at 30° for 30 minutes per session over one 8-hour shift was monitored pre- and post-session for blood pressure, heart rate, respiratory rate, temperature, oxygen saturation, and pain (Numeric Rating Scale). Serial improvements were observed: blood pressure decreased from 149/90 to 111/84 mmHg, heart rate from 113 to 89 beats/min, SpO₂ increased from 95% to 99%, temperature rose from 35.9 to 36.6 °C, respiratory rate remained stable (20→19/min), and pain declined stepwise (NRS 6→5→4) with subsequent patient report of no headache. Intracranial pressure and cerebral perfusion pressure were not directly measured; inferences about cerebral physiology are therefore indirect and based on hemodynamic and symptomatic trends. Within the constraints of a single-subject design, the 30° head-up position appeared feasible, safe, and clinically useful for symptom relief and physiologic stabilization in hemodynamically stable mild head injury, while warranting caution in patients at risk of reduced MAP/CPP or with cervical contraindications. Larger comparative studies are needed to confirm these effects.